Encapsulation of Moringa oleifera Extract in Ca-Alginate Chocolate Beads: Physical and Antioxidant Properties - Olga Kaltsa; Aggeliki Alibade; Eleni Bozinou; Dimitris P. Makris; Stavros I. Lalas (Journal of Food Quality)
The aim of the present study was to evaluate the physical and antioxidant properties of chocolate alginate beads containing Moringa oleifera leaf extract (MLE) produced with ecofriendly solvent extraction technology (Deep Eutectic Solvents). The concentration of MLE incorporated was 0, 2, 4, and 6% w/w, and hardening time for ionotropic gelation with CaCl2 solution was 2, 8, or 20 min. Freshly prepared beads were evaluated for their geometric (area, perimeter, ferret diameter, circularity, roundness), color (CIE L∗, a∗, and b∗ and chroma), and antioxidant properties (total phenolic content and percentage inhibition of DPPH• radical). Increasing the MLE concentration resulted in beads smaller in size and more spherical, whereas hardening time only affected their circularity. MLE concentration had also a profound effect on color and antioxidant properties of the beads. As the concentration of MLE increased, the beads appeared lighter and their chroma increased. The radical scavenging activity was ameliorated by the MLE concentration increase for samples hardened for 8 and 20 min, whereas it was unaffected for those at 2 min. The hardening time on the contrary did not affect the inhibition of DPPH• values, regardless of the amount of extract added.